A study of bantu retail traders in certain areas of the Eastern Cape - Savage, R B (Rhodes University, Faculty of Commerce, Department of Economics, 1967)
The beginning of the eighteenth century marks the start of economic relations between the colonists of the Cape and the Bantu. As early as 1702 a quarrel about the bartering of cattle had broken out between parties of Whites and Bantu, each of which had made their way, from opposite directions, into the area between the Gamtoos and the Kei Rivers. The Bantu, who were encountered in the Eastern Cape, belonged to the Xhosa-speaking tribes. They were cattle farmers who also practised some agriculture, but this was considered a subsidiary activity which was left to the women. Their economy was a self-sufficient subsistence one with each family an almost entirely self-supporting unit. Each relied on its own cattle and crops and built its own dwellings. To serve its own requirements, each family made domestic utensils out of wood, grass and clay. Iron implements were, however, made by special smiths.
Keywords: Retail trade -- Bantu-speaking peoples -- South Africa -- Eastern Cape; Black people -- South Africa -- Eastern Cape